New insights into the early stages of silica-controlled barium carbonate crystallisation - Eiblmeier, J.; Schürmann, U.; Kienle, L.; Gebauer, Denis; Kunz, W.; Kellermeier, M. (R S C Publications, 2014)
© The Royal Society of Chemistry.Recent work has demonstrated that the dynamic interplay between silica and carbonate during co-precipitation can result in the self-assembly of unusual, highly complex crystal architectures with morphologies and textures resembling those typically displayed by biogenic minerals. These so-called biomorphs were shown to be composed of uniform elongated carbonate nanoparticles that are arranged according to a specific order over mesoscopic scales. In the present study, we have investigated the circumstances leading to the continuous formation and stabilisation of such well-defined nanometric building units in these inorganic systems. For this purpose, in situ potentiometric titration measurements were carried out in order to monitor and quantify the influence of silica on both the nucleation and early growth stages of barium carbonate crystallisation in alkaline media at constant pH. Complementarily, the nature and composition of particles occurring at different times in samples under various conditions were characterised ex situ by means of high-resolution electron microscopy and elemental analysis. The collected data clearly evidence that added silica affects carbonate crystallisation from the very beginning (i.e. already prior to, during, and shortly after nucleation), eventually arresting growth on the nanoscale by cementation of BaCO3 particles within a siliceous matrix. Our findings thus shed light on the fundamental processes driving bottom-up self-organisation in silica-carbonate materials and, for the first time, provide direct experimental proof that silicate species are responsible for the miniaturisation of carbonate crystals during growth of biomorphs, hence confirming previously discussed theoretical models for their formation mechanism. This journal is